Do patron bans affect subsequent behaviour? An examination of pre‐ and post‐ban offending for barring notice and prohibition order recipients in Western Australia. (12th March 2023) - Farmer, Clare; Miller, Peter G.; Taylor, Nicholas; Baldwin, Ryan
Abstract: Introduction: To explore whether receipt of either of two patron banning provisions currently used in Western Australia—in response to alcohol‐related disorderly and anti‐social behaviour—is associated with changes to subsequent offending. Method: Western Australia Police de‐identified the offender records and associated data for 3440 individuals who had received one or more police‐imposed barring notice/s between 2011 and 2020, and 319 individuals who had received one or more prohibition orders between 2013 and 2020. The number of offences recorded for each recipient before and after the first notice/order were examined to understand the potential effect of both provisions upon subsequent offending. Results: The low number of repeat barring notices (5% of the total) and prohibition orders (1% of the total) points to their general success. Analysis of offending records before and after receipt/expiry of either provision indicates that both have a generally positive effect on subsequent behaviours. For all barring notice recipients, 52% recorded no further offences and for all prohibition order recipients, 58% recorded no further offences. There was a less positive effect for the sub‐set of multiple ban recipients and prolific offenders. Discussion and Conclusions: Barring notices and prohibition orders appear to have a generally positive effect on subsequent behaviours for the majority of recipients. More targeted interventions are recommended for repeat offenders, for whom patron banning provisions have a more limited effect.